Combinatorial structures associated with some classes of Leibniz algebras - Said Husain, Sharifah Kartini; Ahmad Jamri, Ayu Ameliatul Shahilah; Rakhimov, Isamiddin Sattarovich (AIP Publishing, 2016)
This paper gives a graphical representation of a subclass of complex filiform Leibniz algebras. This class is split into three subclasses called first, second and third class denoted, in dimension n over a field of complex numbers ℂ, by FLbn(ℂ), SLbn(ℂ) and TLbn(ℂ), respectively. Here, the combinatorial structures associated with FLbn(ℂ) and SLbn(ℂ) in low dimensions are considered and some structural properties of the combinatorial structures are given.